Practical Strategies to Increase Teacher and Staff Job Satisfaction at “Yayasan Anak Global Indonesia, Jakarta” - Hernita Kurniawan; Tin Agustina; Dany Moenindyah Handarini (Jurnal Ilmiah Bisnis dan Ekonomi Asia)
Teacher job satisfaction is one of the factors that must be considered. If teachers feel satisfied with their work, an atmosphere of togetherness will be created; they will have the same responsibility, a good communication climate, and high work enthusiasm to achieve school goals optimally. Likewise, school staff have an essential role in supporting school teaching and learning activities. This study aimed to determine practical strategies for improving teacher and staff job satisfaction at the Yayasan Anak Global Indonesia, Jakarta. The instrument used was a questionnaire distributed to 32 teachers and staff through a saturated sample sampling technique. Using multiple linear regression analysis, all hypotheses were finally tested and proven. It was found that practical strategies to improve job satisfaction are to optimize the work environment, make the organizational culture positive, and improve interpersonal communication between teachers and staff. This study is limited to one school only, so it cannot be generalized to all schools. Further research is expected to expand the research area, not only in 1 school, and differentiate between teachers and staff because they have different roles